2017
DOI: 10.1016/j.envres.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cancer in small geographical areas and proximity to air-polluting industries

Abstract: Aim Pediatric cancer has been associated with exposure to certain environmental carcinogens. The purpose of this work is to analyse the relationship between environmental pollution and pediatric cancer risk. Method We analysed all incidences of pediatric cancer (< 15) diagnosed in a Spanish region during the period 1998–2015. The place of residence of each patient and the exact geographical coordinates of main industrial facilities was codified in order to analyse the spatial distribution of cases of cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…During 2015, Ramis et al published a case-control study with spatial analysis, which included cases of leukemia, cancer of the CNS and non-Hodgkin’s lymphoma from five regions of Spain diagnosed from 1996 to 2011, and reported absence of any statistically significant cluster [46]. Ortega-García and cols., analyzed the spatial distribution of all incident cases of CC diagnosed in Spain during 1998 to 2015, using focused cluster tests and found a possible association between proximity to certain industries and CC [10]. Previous population case-control studies conducted in Spain by same research team reported an increased risk of Leukemia in children (OR: 1.31, 95% CI: 1.03-1.67) [5], and renal tumors (OR: 1.97, 95% CI: 1.13-3, 42) [47] associated with living at a distance less than 2.5 km from industrial facilities; increased risk of neuroblastomas associated with industrial facilities at 1 km (OR: 2.52; 95% CI: 1.20-5.30) and 2 km (OR: 1.99; 95% CI: 1.17-3.37) [48]; and increased risk of bone tumors in children under 15 years of age associated with living less than 3 km from industrial sources (OR: 2.33; 95% CI: 1.17-4.63) [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During 2015, Ramis et al published a case-control study with spatial analysis, which included cases of leukemia, cancer of the CNS and non-Hodgkin’s lymphoma from five regions of Spain diagnosed from 1996 to 2011, and reported absence of any statistically significant cluster [46]. Ortega-García and cols., analyzed the spatial distribution of all incident cases of CC diagnosed in Spain during 1998 to 2015, using focused cluster tests and found a possible association between proximity to certain industries and CC [10]. Previous population case-control studies conducted in Spain by same research team reported an increased risk of Leukemia in children (OR: 1.31, 95% CI: 1.03-1.67) [5], and renal tumors (OR: 1.97, 95% CI: 1.13-3, 42) [47] associated with living at a distance less than 2.5 km from industrial facilities; increased risk of neuroblastomas associated with industrial facilities at 1 km (OR: 2.52; 95% CI: 1.20-5.30) and 2 km (OR: 1.99; 95% CI: 1.17-3.37) [48]; and increased risk of bone tumors in children under 15 years of age associated with living less than 3 km from industrial sources (OR: 2.33; 95% CI: 1.17-4.63) [49].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors argue that environmental factors can be the cause of 85-96% of all cancers in childhood [4] [5] [6] [7]. In recent years, studies conducted in England, Spain and the United States found an association between CC, especially leukemia and CNS tumors, and air pollution exposure [8] [9] [10]. Air pollution is considered the world’s largest single environmental health risk as the World Health Organization (WHO, 2016) affirmed that 92% of the world population lives in places where air quality levels are poor [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors argue that environmental factors can be the cause of 85%‐96% of all cancers in childhood 4‐7 . In recent years, studies conducted in England, Spain and the United States found an association between CC, especially leukemia and neoplasms of the central nervous system tumors, and air pollution exposure 8‐10 . Air pollution is the world's largest single environmental health risk; it is the presence in the air of one or more substances in a concentration or a duration exceeding their natural levels, with the possibility of producing an adverse effect 11…”
Section: Introductionmentioning
confidence: 99%
“…In some regions located in the vicinity of air pollution sources (i.e. industrial sites), researchers have noticed higher [3], which is aggravated by vehicle exhaust air [4]. Therefore, complex pollution is extremely dangerous [5,6].…”
Section: Introductionmentioning
confidence: 99%